Gender Differences in General Health Checkup Utilization: A Three-Year Retrospective Study in a Multispecialty Hospital in Kathmandu, Nepal - Iru Poudel; Raji Shrestha; Sujit Banskota (NPRC Journal of Multidisciplinary Research, 2026)
Background: General health checkups (GHCs) are an important component of preventive healthcare, facilitating routine health assessment and the early identification of potential health risks. Evidence regarding gender differences in the utilization of preventive health checkups in Nepal remains limited. Objective: This study aimed to assess gender differences in GHC utilization over three consecutive fiscal years and to compare changes in GHC volume with overall outpatient department (OPD) volume. Materials and Methods: A retrospective descriptive trend analysis was conducted using anonymized electronic health record data from a multispecialty hospital in Kathmandu, Nepal. All patients who completed standardized GHC packages during fiscal years 2080/81, 2081/82, and 2082/83 were included. Patients receiving routine OPD care, specialty consultations, follow-up services, emergency care, or isolated diagnostic services outside GHC packages were excluded. Descriptive analyses were performed according to fiscal year and gender, and changes in GHC and total OPD volumes were calculated. Results: Total GHC utilization increased from 937 cases in FY 2080/81 to 1,092 in FY 2081/82 and 1,109 in FY 2082/83, representing an overall increase of 18.36%. Female utilization increased consistently from 550 to 592 and 611 cases, whereas male utilization increased from 387 to 500 cases before declining slightly to 498 cases. Females accounted for 58.70%, 54.21%, and 55.09% of total GHC utilization across the three fiscal years, respectively. In comparison, total OPD volume increased from 119,598 patients in FY 2080/81 to 124,168 in FY 2082/83, representing a 3.82% increase. GHCs accounted for 0.783%, 0.883%, and 0.893% of total OPD volume, respectively. Conclusion: GHC utilization increased over the three-year study period at a greater relative rate than overall OPD volume. Female patients consistently accounted for a larger proportion of GHC utilization than male patients. Despite this increase, GHCs represented less than 1% of total OPD activity in each fiscal year. Further research incorporating demographic, socioeconomic, behavioral, and healthcare-access variables is warranted to identify factors associated with gender differences in preventive healthcare utilization and to inform strategies for improving equitable access to GHC services. Novelty: This study provides the first multi-year, electronic medical record-based trend analysis of preventive health checkup utilization and gender-based disparities within a Nepalese multispecialty hospital context.